NGOs nook - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
FAO s new Webpage designed to make FAO s online information and services more accessible to NGOs, will be useful not only for NGOs but also for other people and organisations. It shows the virtual visitor around the FAO, provides contact details...